GPER-1 Rapid Regulation Influences p-Akt Expression to Resist Stress-Induced Injuries in a Sex-Specific Manner - Sang, L; Fu, L; Gao, L; Adu-Amankwaah, J; Gong, Z; Li, T; Ma, Z; Wang, Z; Xu, J; Sun, H (Physiological research, 2024)
G protein-coupled estrogen receptor 1 (GPER-1) has gained recognition for its role in conferring cardioprotection. However, the extent to which GPER-1 exerts equally important effects in both sexes remains unclear. The study found similar expressions of GPER-1 in rat heart apex in both sexes. In male rats, administering epinephrine (Epi) at a dose of 31.36 microg/100 g resulted in a rapid decline in cardiac function, accompanied by a sharp increase in bax/bcl-2 levels. In contrast, female rats did not display significant changes in cardiac function under the same conditions. Additionally, compared to the injection of Epi alone (at a dose of 15.68 microg/100 g), the administration of G15 (GPER-1 antagonist) further decreased cardiac function in both male and female rats. However, it only increased mortality and lung coefficient in male rats. Conversely, G1 (GPER-1 agonist) administration improved cardiac function in both sexes. Notably, the apex of the male heart exhibited lower levels of inhibitory G protein (Galphai). Furthermore, female and male rats treated with Epi displayed elevated phosphorylated protein kinase B (p-Akt). Compared to their respective Epi groups, the administration of G15 increased p-Akt levels in female rat hearts but decreased them in male rat hearts. Conversely, the administration of G1 decreased p-Akt levels in females but rapidly increased them in male rats. Our study uncovers the vital role of GPER-1 in protecting against stress-induced heart injuries in a sex-specific manner. These findings hold immense potential for advancing targeted cardiac therapies and enhancing outcomes for both females and males.
Keywords: receptory pro estrogeny; Receptors, G-Protein-Coupled; Receptors, Estrogen; Male; potkani Sprague-Dawley; Sex Characteristics; sexuální faktory; protoonkogenní proteiny c-akt; Proto-Oncogene Proteins c-akt; mužské pohlaví; pohlavní dimorfismus; Stress, Physiological; adrenalin; krysa rodu Rattus; Epinephrine; Animals; ženské pohlaví; zvířata; Sex Factors; Rats; receptory spřažené s G-proteiny; Female; fyziologický stres; Rats, Sprague-Dawley